Macrophage death and defective inflammation resolution in atherosclerosis - Tabas, Ira (2009)
A key event in atherosclerosis is a maladaptive inflammatory response to subendothelial lipoproteins. A critical aspect of this response is failure of inflammation resolution, which normally consists of suppression of inflammatory cell influx, effective clearance of apoptotic cells (efferocytosis), and promotion of inflammatory cell egress. Defects in these processes promote the progression of atherosclerotic lesions into dangerous plaques, which can trigger atherothrombotic vascular disease, the leading cause of death in industrialized societies. This review will provide an overview of these concepts, with a focus on macrophage death, defective efferocytosis, and novel therapeutic strategies designed to boost inflammation resolution in atherosclerosis.